Perencanaan Pajak Penghasilan Pasal 21 PT 8wood International Group - Sumarno Manrejo; Theo Ariandyen (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
The purpose of this study was to determine the implementation and planning of Article 21 PPh of PT 8Wood Internasional Group in an effort to obtain tax saving. Methodology The research method used is descriptive with a quantitative approach. The findings of the study show that if the company uses the Gross Up Method, the burden of PPh 21 is the largest compared to other methods. With the gross up method, it seems that the amount of Article 21 income tax is the largest, but this amount will be eliminated because the company can finance it. The gross up policy given to employees is expected to increase work enthusiasm. Suggestions Practical implications for companies are described in this study.